Event attendance system using bar code scanner / Mohd Syafiq Azmi Zulhisham - Zulhisham, Mohd Syafiq Azmi (2017)
The purpose or intention in conducting this project was to ease the process of taking the attendance of an event and as well as helps Unit Kolej in calculate the merit points of students who stay in college. Unit Kolej is one of the stakeholders for this system. This system consists of three users or actors which interact within it which are upk, club, and student. Currently, the process of management of event and calculate the students merit points are done manually by using paper based with very small computerize element. Therefore, in order to tackle those problem, the objective have been identified that lead to the conducting of this research. In order to supervise all the process, a framework or methodology have been chosen which are waterfall methodology. Based on data analysis process, it can be identified that element of bar code in this project helps a lot in the process of taking attendance in order to avoid congestion at the attendance counter. Eventhough this project have been completed, but there are a lot of enhancements that can be done in every aspect in order to improve it. As an example are by widening the scope of this research which are not only limited to students who stay college but also the Non Residence (NR). Besides that, it can also be done by increasing the functionalities of the system and integrate the system with the current system used by the student affairs (HEP) and also addressing the important of testing phase. In conclusion, this project proved to be beneficial to the stakeholder in many way.